“Many of them are among my best men”: The United States Navy looks at its African American crewmen, 1755-1955 - Davis, Michael Shawn (Kansas State University, 2011)
ABSTRACT Historians of the integration of the American military and African American military participation have argued that the post-World War II period was the critical period for the integration of the U.S. Navy. This dissertation argues that World War II was “the” critical period for the integration of the Navy because, in addition to forcing the Navy to change its racial policy, the war altered the Navy’s attitudes towards its African American personnel. African Americans have a long history in the U.S. Navy. In the period between the French and Indian War and the Civil War, African Americans served in the Navy because whites would not. This is especially true of the peacetime service, where conditions, pay, and discipline dissuaded most whites from enlisting. During the Civil War, a substantial number of escaped slaves and other African Americans served. Reliance on racially integrated crews survived beyond the Civil War and the abolition of slavery, only to succumb to the principle of “separate but equal,” validated by the Supreme Court in the Plessy case (1896). As racial segregation took hold and the era of “Jim Crow” began, the Navy separated the races, a task completed by the time America entered World War I. The Navy paid the price in lost efficiency to maintain the policy. After the war, the Navy chose to accept African Americans solely for duty as messmen and stewards. Matters changed in World War II. The Navy eventually lifted its restrictions on African American enlistment and promotions, commissioned its first African American officers, and finally committed itself to a program of integration. The increased interaction between whites and African Americans had also led to white officers and policymakers re-assessing the value of African American sailors, a crucial sine qua non for the actualization of integration in the postwar years.
Keywords: African American; U.S. Navy; Integration; World War II; Naval policy; Racism; History, Black (0328); History, United States (0337); Sociology, Ethnic and Racial Studies (0631)